2007
DOI: 10.1111/j.1365-2036.2007.03532.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: endoscopic dilatation in Crohn’s disease

Abstract: SUMMARY BackgroundEndoscopic dilatation for Crohn's disease has been evaluated only in some small and heterogeneous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
210
4
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(235 citation statements)
references
References 33 publications
13
210
4
8
Order By: Relevance
“…Endoscopy can also serve a therapeutic role in the dilation of strictures, particularly those at a surgical anastomosis, although double-blind, sham-controlled trials are lacking (50,51) . A recent systematic review suggested that those patients who bene t most from endoscopic balloon dilation have short (less than 4 cm) postsurgical anastomotic strictures (52) . e use of adjunctive corticosteroid injection into strictures at the time of balloon dilation was not e ective (53) .…”
Section: Generalmentioning
confidence: 99%
“…Endoscopy can also serve a therapeutic role in the dilation of strictures, particularly those at a surgical anastomosis, although double-blind, sham-controlled trials are lacking (50,51) . A recent systematic review suggested that those patients who bene t most from endoscopic balloon dilation have short (less than 4 cm) postsurgical anastomotic strictures (52) . e use of adjunctive corticosteroid injection into strictures at the time of balloon dilation was not e ective (53) .…”
Section: Generalmentioning
confidence: 99%
“…Perforation rates in benign gastric outlet obstruction are high as 7.4%, risk factors are dilation in the setting of active ulceration and balloon size greater than 15 mm [42]. In lower gastrointestinal strictures' dilation, mostly in anastomosis and in Crohn's disease, the perforation is more often reported with 25 mm balloons [43,44].…”
Section: Dilationmentioning
confidence: 99%
“…On the other hand, recurrent symptoms frequently make it necessary to repeat the procedure. In detail, 59% of patients avoided surgery and repeat endoscopy until the end of follow-up, 22% required two sessions, while the remaining 19% required more than two dilatations [8]. This is probably due to the fact that symptomatic CD strictures are not purely fibrotic, but are muscular as well, which might explain the tendency to be resistant to dilatation.…”
Section: Safety and Efficacymentioning
confidence: 99%
“…In the only systematic review available, a multivariate statistical analysis was performed on a simulated population from the available studies up to 2007 [8]. The study found that mostly postsurgical strictures were dilated with a technical success rate of 86%, and long-term efficacy was achieved in 58% of patients, with a mean multivariate analysis in the earlier mentioned systematic review, a stricture length of ≤4 cm was associated with a surgery-free outcome, and this was the only predictor that showed statistical significance: naïve vs. postsurgical strictures, active vs. inactive disease, and sedation vs. anesthesia; possibility to pass the scope after dilatation or balloon caliber (above/below 20 mm) showed no influence on the technical success or the efficacy after dilatation [8]. EBD can be painful; therefore, sedation with a mixture of benzodiazepine and pethidin is recommended by most authors.…”
Section: Safety and Efficacymentioning
confidence: 99%